Factors Related to the Incidence of Diabetes Mellitus at the Trauma Health Center in Samarinda City - Bernadetha, Bernadetha; Palin T, Yona; Satriani, Satriani (Malikussaleh University, Aceh, Indonesia, 2024)
A functional disorder known as diabetes mellitus results in a lack of insulin hormone, either because the pancreas is unable to produce it or because body cells are unable to properly utilize the insulin the pancreas has produced. Because of this disorder, blood sugar levels will rise uncontrollably. Continuously high glucose levels will poison the body, including its organs. The 2018 Riskesdas statistics show that 2% of Indonesians over the age of 15 have been diagnosed with diabetes mellitus. Compared to the 1.5% prevalence of DM in the 2015 Riskesdas data, this figure indicates a rise. Nonetheless, blood sugar levels rose from 6.9% to 8.5% in 2018 based on data from tests conducted in 2013. According to this statistic, about 25% of DM patients are aware that they have the disease. Finding the diabetes mellitus risk variables at the Trauma Center Health Center in Samarinda City is the aim of this study. The study uses a cross-sectional analytical survey that is directed at all 189 patients at the Trauma Center Health Center in Samarinda City who have diabetes mellitus. The study uses unintentional sampling and a questionnaire to gather data. To examine the data for persons with diabetes, we employ the chi square test at a 5% confidence level.